The Use of Problem Based Interactive Video Quizzes to Improve Students Chemical Literacy on the Topic of Water Pollution - Adhwa, Jauza Bahira; Sunarya*, Risa Rahmawati; Sari, Sari; Farida, Ida; Izzulhaq, Brilliant Dwi (Jurnal IPA & Pembelajaran IPA, 2025)
This study is grounded in the importance of students having chemistry literacy related to the issue of water pollution through problem-based learning (PBL) integrated with interactive video quizzes. The purpose of the research was to describe the use of problem-based interactive video quizzes and to analyze the improvement of students chemistry literacy on the topic of water pollution. The research design employed a one-group pretest-posttest with 31 tenth-grade students from a secondary school in West Java as subjects. The instrument used was a chemistry literacy test measuring the aspects of content, context, process, and attitude toward water pollution. The results showed the highest N-Gain increase in the attitude indicator (0.70), followed by context (0.65), content (0.62), and process (0.58). Based on these findings, it can be concluded that the use of PBL integrated with interactive video quizzes can significantly improve students chemistry literacy, with the highest improvement observed in the attitude aspect and the lowest in the process aspect